Characterization and Genetic Analysis of Rice Mutant crr1 Exhibiting Compromised Non-host Resistance to Puccinia striiformis f. sp. tritici (Pst) - Zhao, Jing; Yang, Yuheng; Yang, Donghe; Cheng, Yulin; Jiao, Min; Zhan, Gangming; Zhang, Hongchang; Wang, Junyi; Zhou, Kai; Huang, Lili; Kang, Zhensheng (Frontiers in Plant Science, 2016)
Wheat stripe rust, caused by Puccina striiformis f. sp. tritici (Pst), is one of the most devastating diseases of wheat in China. Rapid change to virulence following release of resistant cultivars necessitates ongoing discovery and exploitation of new resistance resources. Considerable effort has been directed at nonhost resistance (NHR) which is believed to be durable. In the present study we identified rice mutant crr1 (compromised resistance to rust 1) that exhibited compromised NHR to Pst. Compared with wild type rice variety Nipponbare, crr1 mutant displayed a three-fold increase in penetration rates by Pst, and enhanced hyphal growth. The pathogen also developed haustoria in crr1 mesophyll cells, but failed to sporulate. The response to the adapted rice pathogen Magnaporthe oryzae was unchanged in crr1 relative to the wild type. Several defense-related genes involved in the SA- and JA-mediated defense pathways response and in phytoalexin synthesis (such as OsPR1a, OsLOX1, and OsCPS4) were more rapidly and strongly induced in infected crr1 leaves than in the wild type, suggesting that other layers of defense still in effect. Genetic analysis and mapping located the mutant loci at a region between markers ID14 and RM25792, which cover about 290 kb genome sequence on chromosome 10. Further fine mapping and cloning of the locus should provide further insights into NHR to rust fungi in rice, and may reveal new strategies for improving rust resistance in wheat.